Preparation method and application of nitrogen-doped carbon-coated non-noble bimetal honeycomb core-shell catalyst

Non -precious dual -metal honeycomb nuclear shell catalysts covered by nitrogen doped charcoal solve the problem of high cost and low selectivity of precious metal catalysts, and realize the efficient catalytic nitrohrium hydrogen to prepare aniline under mild conditions. Selectability and cycle stability.

CN119327499APending Publication Date: 2025-01-21XIANGTAN UNIV

Patent Information

Application Number
CN202411444071.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-25
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The noble metal catalyst has high cost and low selectivity in the preparation of aniline in the hydrogenation of nitrobenzene, and the reaction conditions of the non-precious metal catalyst are harsh and the metal is prone to agglomeration and leaching.

Method used

Non -precious dual -metal honeycomb nuclear shell catalysts covered with nitrogen doped charcoal, soaking and thermal solution of the dual -metal organic skeleton in the semi -polymer glucose solution to form a catalyst. , Increase active metal decentralization and pore rates of catalysts.

Benefits of technology

Under mild conditions, it is efficiently catalyzed to prepare aniline to prepare nitrate phenyl hydrogen. The nitrobenzene is fully transformed. The aniline selectivity> 99%, high circulation stability, and excellent activity for other aroma nitrate compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327499A_ABST
    Figure CN119327499A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a nitrogen-doped carbon coated non-noble bimetal honeycomb core-shell catalyst. The method comprises the following steps: stirring soluble metal salt and imidazole ligands in an aqueous solution to react to synthesize a double-center metal framework material, one is zinc, and the other is cobalt, iron or nickel; soaking the metal organic framework in a semi-polymerized glucose solution in a low-pressure environment to form a core-shell type compound; and calcining the compound in a nitrogen atmosphere to obtain the catalyst. Compared with a traditional supported metal catalyst, the catalyst provided by the invention has the advantages that the mesoporous rate is high, the size is wide, active sites are uniformly dispersed, the catalyst shows excellent performance in a reaction for preparing aniline through nitrobenzene hydrogenation, and complete conversion of nitrobenzene gt can be realized under mild conditions; the aniline yield is 99%. The preparation process of the catalyst is short in time consumption and high in yield, no by-product or waste is generated, the catalyst also has excellent selectivity on the aromatic nitro compound, and the selectivity of the corresponding amino product can reach 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a preparation method of a nitrogen-doped carbon-coated non-precious bimetallic honeycomb core-shell catalyst and application thereof in the hydrogenation of nitrobenzene to prepare aniline. Background Art

[0002] Aniline can be widely used in the production of chemical products including medicines, pesticides, dyes, resins, etc. The efficient production of aniline is of great significance to fine chemicals and its affiliated industries. The traditional stoichiometric method for producing aniline will produce a large amount of harmful substances, posing a serious threat to human health and the natural environment. Liquid-phase catalytic nitrobenzene hydrogenation has a low reaction temperature and high product purity. It is the most promising mild method for aniline production. 85% of aniline is produced by nitrobenzene hydrogenation process. The key lies in the development of highly active and stable catalysts. Hydrogen has a wide source, is clean and pollution-free. The synthesis of aniline based on high-pressure hydrogen catalytic nitrobenzene hydrogenation under the action of catalysts has the advantages of high conversion rate, good selectivity, and environmental friendliness, and has been used in commercial production.

[0003] Catalysts with noble metal active centers such as Pt, Pd, and Ru are being gradually developed. Chinese invention CN115501886B discloses a method for synthesizing aniline by hydrogenation of nitrobenzene at low temperature. The method uses nitrobenzene as a raw material and hydrogen as a hydrogen source. In the presence of a non-noble metal supported palladium catalyst, nitrobenzene is efficiently converted into aniline. The hydrogen pressure in the reaction medium is 1 to 10 bar, the reaction temperature is 0 to 30°C, and the reaction is carried out in a closed container for 0.5 to 5 hours. However, noble metal catalysts have the disadvantages of high production cost, easy metal loss, and difficulty in catalyst recovery. Finding an economical and green efficient catalyst is the key to solving the above problems. Non-noble metal catalysts have abundant reserves and low costs, and also have excellent activity in nitrobenzene hydrogenation. Loading non-noble metals on appropriate carriers can effectively disperse metal active sites. In particular, core-shell catalysts can not only inhibit the agglomeration and leaching of metal active components, but also have unique catalytic behavior. The literature (Science, 2016, 352: 974-978) reported that SiO 2 The core-shell catalysts prepared by the sacrificial template method show better catalytic activity, lower metal loading, and higher stability than commercial catalysts, but this type of core-shell structured catalyst usually consumes a large amount of template agents, and the preparation process is relatively cumbersome.

[0004] Porous carbon-supported metal catalysts have the advantages of high porosity and good electrical conductivity. In particular, nitrogen-doped carbon can effectively adjust the charge difference between active metals and carriers and anchor active metals, thereby improving catalytic activity. Chinese patent CN 113952977B discloses a method for preparing a nitrogen-doped carbon-coated precious metal catalyst, wherein the catalyst is obtained by impregnating precious metals with activated carbon, reducing with hydrogen, coating with polymers, and performing secondary pyrolysis. The catalyst has high activity and stability in the synthesis of aniline from nitrobenzene, the synthesis of CLT acid from 2-nitro-4-methyl-5-chlorobenzenesulfonic acid, and the synthesis of p-aminobenzenesulfonic acid from p-nitrobenzenesulfonic acid. It can be foreseen that core-shell catalysts are a class of catalysts with great potential in the hydrogenation reaction of nitrobenzene, but the above method includes complex processes such as metal impregnation, high-temperature reduction, and secondary pyrolysis. The uneven pore size of activated carbon is also prone to agglomeration during metal impregnation. In order to solve the problem of active metal agglomeration, a bimetallic strategy can be considered to improve the dispersion of active metals. The presence of inert metals can effectively isolate active metals and affect electronic structure characteristics. The literature (Green Chem. 2015, 17: 821-826.) used fir sawdust to preload Ni-Fe bimetallic salt and then pyrolyze to obtain Ni-NiFe 2 O 4 / CNF catalyst, the catalyst can achieve complete conversion of nitrobenzene under 1MPa hydrogen pressure, but it needs to react at 150°C for 2h and the catalyst dosage is 100mg. The system has high reaction temperature, long reaction time, and large catalyst dosage, which is not suitable for industrial production. The literature (Fuel Process Technol., 2023, 240: 107559) obtains a nickel-loaded carbon-based catalyst by in-situ pyrolysis of nickel and zinc-organic complexes and uses it for hydrogenation of levulinic acid. The self-volatilization effect of metallic zinc during pyrolysis gives the catalyst a higher specific surface area, but its activity decreases significantly in the cycle test, indicating that the catalyst pore structure is unstable, easily destroyed during the reaction, and the metal dispersion is not high.

[0005] As the concept of green chemistry has gained popularity, exploring the application of a type of non-precious metal catalyst with simple process, high activity and good stability in the hydrogenation of nitrobenzene has become a popular direction. Metal-organic frameworks are a type of crystalline material in which metal ions and ligands are bound by coordination bonds. They have high metal dispersion and rich pore structure, and can generate carbon catalysts rich in metal sites by in-situ pyrolysis. Compared with traditional catalysts, metal-organic framework-based catalysts have abundant active metal sites and high dispersion. The catalysts prepared by combining the advantages of metal-organic frameworks, core-shell structures, and carbon carriers can effectively solve the problems of easy metal agglomeration and escape, low catalyst selectivity, and poor stability during the hydrogenation of nitrobenzene. Therefore, this method intends to use a bimetallic organic framework as a carrier, coat an amorphous carbon shell layer on its surface, and in situ pyrolyze to form a nitrogen-doped carbon-coated non-precious bimetallic honeycomb core-shell catalyst. The self-volatilization effect of metallic zinc at high temperature is used to obtain a catalyst with high porosity and honeycomb structure. The core-shell structure can effectively inhibit the metal escape in the reaction. The synergistic effect between the bimetallics can increase the dispersion of the active metal and improve its electronic structure characteristics, thereby increasing the activity of the catalyst, and ultimately realizing the process of selective catalytic hydrogenation of nitrobenzene to prepare aniline. Summary of the invention

[0006] The technical problem to be solved by the present invention is: in view of the high cost and low selectivity of precious metal catalysts in the process of hydrogenating nitrobenzene to prepare aniline, the harsh reaction conditions of non-precious metal catalysts, and the easy agglomeration and leaching of metals, a nitrogen-doped carbon-coated non-precious bimetallic honeycomb core-shell catalyst is developed to realize the production process of efficiently catalyzing the hydrogenation of nitrobenzene to prepare aniline.

[0007] The technical problem solved by the present invention is achieved through the following technical solutions:

[0008] A method for preparing a non-precious bimetallic honeycomb core-shell catalyst coated with nitrogen-doped carbon, characterized in that a bimetallic organic framework is immersed in a semi-polymerized glucose solution to form a composite precursor, which is in situ pyrolyzed to obtain a honeycomb core-shell catalyst coated with an amorphous carbon layer, wherein one metal is zinc and the other metal is cobalt, iron or nickel. The honeycomb structure of the catalyst is generated by the self-volatilization effect of metallic zinc during high-temperature pyrolysis. The presence of zinc can increase the specific surface area of ​​the catalyst and reduce the agglomeration of active metals; the amorphous carbon shell formed by semi-polymerized glucose can slow down metal oxidation, agglomeration and escape, and increase the carbon content in the catalyst carrier. Adding triethylamine when synthesizing a metal organic framework in an aqueous solvent can effectively enhance the binding ability of the metal and the ligand, realize the rapid synthesis of the metal organic framework and improve the yield. Compared with traditional synthesis methods, no other organic solvents are required, which is green and environmentally friendly.

[0009] The catalyst exhibits excellent performance in preparing aniline by hydrogenating nitrobenzene under mild conditions. The preparation method of the catalyst is implemented according to the following steps:

[0010] (1) Synthesis of a dual-center metal organic framework: two soluble metal salts are dissolved in deionized water to form a solution A, and imidazole ligands and an appropriate amount of triethylamine are dissolved in deionized water and stirred to form a solution B; solutions A and B are rapidly mixed and stirred for 30 to 120 minutes at room temperature, and then centrifuged, washed, and vacuum dried to obtain a dual-center metal organic framework;

[0011] (2) Preparation of core-shell composite precursor: Glucose is subjected to low-temperature hydrothermal reaction in a polytetrafluoroethylene-lined reactor to obtain a semi-polymerized glucose solution, which is then transferred to a constant pressure funnel after cooling; the metal organic framework in step (1) is placed in a supported flask and connected to a vacuum pump, which is simultaneously connected to a constant pressure funnel containing the semi-polymerized glucose solution to form a closed low-pressure environment, and the semi-polymerized glucose solution is dripped dropwise, stirred, and the metal organic framework is fully immersed to form a core-shell composite precursor;

[0012] (3) High-temperature calcination process: The core-shell composite precursor in step (2) is centrifugally dried and calcined at high temperature under a nitrogen atmosphere to obtain the catalyst.

[0013] In a specific embodiment, in step (1), one of the metal salts is zinc nitrate and the other is one of cobalt nitrate, cobalt acetate, cobalt chloride, ferric nitrate, ferric chloride, nickel nitrate, nickel acetate, nickel chloride and hydrates of these salts; the ligand is at least one of 2-methylimidazole, 2-nitroimidazole and imidazole-2-carboxaldehyde, and the molar ratio of the metal to the ligand is 1:(2-40); the molar ratio of the amount of the added triethylamine substance to the entire system is 0.001-0.006.

[0014] In a specific embodiment, in step (2), the mass volume ratio of glucose to deionized water is (2-8) g: 60 mL, the hydrothermal temperature is 120-170° C., and the reaction time is 6-24 h. The mass volume ratio of the metal organic framework to the semi-polymerized glucose solution is 1 g: (4-20) mL.

[0015] In a specific embodiment, in step (3), the pyrolysis temperature is 700-1000° C., the heating rate is 1-10° C. / min, and the calcination time is 0.5-6 h.

[0016] The method for applying the catalyst to prepare aniline by hydrogenating nitrobenzene is characterized in that hydrogen is used as a hydrogen source, the catalyst, nitrobenzene and a solvent are stirred and mixed in a reactor, hydrogen is introduced to fully replace the air, the valve is closed after the reaction temperature and hydrogen pressure are set, the reactor is cooled to room temperature after the reaction is completed, the solvent and the catalyst are separated by centrifugation, and the nitrobenzene conversion rate and the aniline yield are tracked by gas chromatography.

[0017] In a specific implementation scheme of the above method, the mass ratio of the catalyst to nitrobenzene is 1: (3-20), the solvent is selected from at least one of methanol, ethanol, propanol, isopropanol, and water; the mass volume ratio of nitrobenzene to the solvent is (0.1-0.6) g: (10-30) mL; the hydrogen pressure is 0.4-1.2 MPa, the reaction temperature is 50-120° C., and the reaction time is 0.5-4 h.

[0018] The characteristics and beneficial effects of the present invention are:

[0019] 1. This method uses water as a solvent in the preparation of a bimetallic organic framework, which is green and environmentally friendly. At the same time, a deprotonating agent, triethylamine, is added to enhance the binding force between the metal and the ligand. The metal organic framework can be rapidly synthesized in 30 minutes with a high yield.

[0020] 2. The zinc in the catalyst increases the spacing between active metal particles and their dispersion. The self-volatilization effect of zinc during high-temperature pyrolysis increases the specific surface area of ​​the catalyst, exposing more active sites, and achieving better catalytic effects. It is also the source of the honeycomb structure of the catalyst. The semi-polymerized glucose coating provides more carbon sources and plays a supporting role during the pyrolysis process, increasing the porosity of the catalyst and promoting the rapid adsorption and diffusion of the reaction substrate near the metal active sites. The carbon shell formed by pyrolysis protects the metal from oxidation and its loss during the reaction process.

[0021] 3. The catalyst provided by the present invention can achieve efficient catalytic hydrogenation of nitrobenzene to prepare aniline under mild conditions, nitrobenzene can be completely converted, aniline selectivity is >99% and there is no metal escape, the cycle is stable and high, and it also has excellent activity for other aromatic nitro compounds, and has important industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the process of the catalyst described in Example 1.

[0023] Figure 2 is a pore size distribution curve of the catalyst described in Example 1.

[0024] Figure 3 The nitrobenzene conversion rate in Example 1 and Comparative Examples 1-2 changes with the reaction time. DETAILED DESCRIPTION

[0025] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the present invention can be implemented in many different ways as limited and covered by the claims.

[0026] Embodiment 1:

[0027] The schematic diagram of the catalyst preparation process is as follows Figure 1 As shown, it mainly includes the following three steps:

[0028] (1) Synthesis of bimetallic organic framework: 1.164 g of cobalt nitrate hexahydrate and 1.188 g of zinc nitrate hexahydrate were dissolved in 60 mL of deionized water, which was called solution A. 5.255 g of 2-methylimidazole and 2 mL of triethylamine were dissolved in 60 mL of deionized water and mixed thoroughly, which was called solution B. Solution A was quickly poured into solution B at room temperature, stirred at 100 r / min for 1 h, and then centrifuged. After washing with deionized water three times, the mixture was dried at 80°C in vacuum for 24 h to obtain a Zn-Co bimetallic organic framework.

[0029] (2) Preparation of core-shell complex: 6 g of glucose was dissolved in 60 mL of water and heated in a reactor at 160° C. for 12 h to obtain a semi-polymerized glucose solution; 40 mL of the semi-polymerized glucose solution was placed in a constant pressure funnel, and the metal organic framework obtained in step (1) was placed in a branched flask and connected to the constant pressure funnel and a vacuum pump, and a vacuum pump was used to create a low pressure environment in the reaction system; the valve of the constant pressure funnel was slowly opened to allow the semi-polymerized glucose to drip into the branched flask drop by drop, and the mixture was stirred and soaked for 24 h to form a core-shell complex, which was centrifugally filtered, washed 3 times, and dried at 80° C. for 24 h to obtain a core-shell complex;

[0030] (4) Calcination process: The core-shell composite precursor described in step (2) is placed in a tubular furnace and nitrogen is introduced to perform pyrolysis at 900°C, with a heating rate of 3°C / min and a constant temperature reaction for 2 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain the catalyst, which is labeled as CoZn@GNC-900.

[0031] Depend on Figure 2 It can be seen that: the pore size distribution of the catalyst is relatively wide and is rich in a large number of mesopores with a pore size of 2-30nm. Take 30mg of the above catalyst, 0.15g of nitrobenzene, and 15mL of anhydrous ethanol and put them in a 50mL high-pressure reactor. Assemble the reactor and use high-purity hydrogen to purge the reaction system three times to fully replace and remove the air in the reactor. Fill the reactor with hydrogen to 0.6MPa, adjust the magnetic stirring to 800r / min, and raise the reaction temperature to 100°C. After 2h of reaction, centrifuge to separate the solid and liquid, and use gas chromatography to track and analyze. The nitrobenzene conversion rate is 100%, and the aniline selectivity is >99%. By Figure 3 It can be seen that the conversion rate of nitrobenzene is greatly affected by the reaction time, and prolonging the reaction time can significantly increase the conversion rate of nitrobenzene.

[0032] Embodiment 2-4:

[0033] The steps of the preparation method of the catalyst in Examples 2-4 are the same as those in Example 1. After obtaining the core-shell composite precursor, a high-temperature calcination reaction is continued to prepare the catalyst. The calcination temperature is set to 700°C, 800°C or 1000°C to obtain the catalyst and used for nitrobenzene hydrogenation. The catalysts are marked as CoZn@GNC-700, CoZn@GNC-800, and CoZn@GNC-1000. The specific application method is the same as that in Example 1. After the reaction is completed, it is naturally cooled to room temperature and samples are taken for gas chromatography detection and analysis. The calcination temperature has a great influence on the catalytic activity of the catalyst in nitrobenzene hydrogenation. The nitrobenzene conversion rate is reduced to 35.3%, 43.7% or 11.6%, respectively, but the aniline selectivity is >99%.

[0034] Embodiment 5:

[0035] The catalyst and reaction conditions in Example 1 were applied to aromatic nitro compounds with other substituted groups. The catalytic detection effects are shown in Table 1. The results show that this type of nitrogen-doped carbon-coated non-precious bimetallic honeycomb core-shell catalyst has high activity for more than ten kinds of aromatic nitro compounds such as o-chloronitrobenzene.

[0036] Table 1 Catalytic detection effect of the catalyst described in Example 1 on aromatic nitro compounds with other substituted groups

[0037]

[0038] According to the test results of Examples 1 to 4, it is found that the calcination temperature in the catalyst preparation process significantly affects the activity of the catalyst under the same hydrogenation conditions. When the calcination temperature is near the boiling point of zinc, due to its self-volatilization effect, a rich honeycomb pore structure can be produced in the catalyst, exposing more active sites, so the catalytic activity of Example 1 is significantly better than that of Examples 2 and 3. In Example 4, the calcination temperature is further increased, and the presence of metal cobalt causes the catalytic graphite structure to be produced at high temperature, and the regular graphite structure becomes more, the original structure is destroyed, and the specific area decreases and the activity decreases.

[0039] Comparative Example 1:

[0040] The preparation process of the catalyst in Comparative Example 1 is the same as that in Example 1, except that the semi-polymerized glucose soaking process in a low-pressure environment described in step (2) is omitted, that is, after the bimetallic organic framework is obtained in step (1), it is directly calcined at high temperature in a nitrogen atmosphere to obtain the catalyst, and the remaining steps are the same as those in Example 1. The gas chromatography analysis results show that the nitrobenzene conversion rate of the catalyst after 2 hours of reaction is only 62.4%, but the selectivity of aniline is also >99%. The test data are listed in Table 2. The trend of nitrobenzene conversion rate with reaction time is as follows: Figure 3 shown.

[0041] Comparative Example 2:

[0042] The preparation process of the catalyst in Comparative Example 2 only involves a single metal cobalt, that is, no inert metal zinc is added, and the remaining implementation steps are the same as those in Example 1. After being soaked in a semi-polymerized glucose solution under a low pressure environment, a core-shell type composite is formed, and a nitrogen-doped carbon-coated single metal core-shell catalyst is obtained by high-temperature calcination. Due to the lack of zinc, the catalyst has a low porosity and does not show a honeycomb structure. The results of gas chromatography analysis show that the nitrobenzene conversion rate of the catalyst after 2 hours of reaction is only 43.1%, and the aniline selectivity is >99%. The test data are listed in Table 2. The trend of nitrobenzene conversion rate with reaction time is as follows: Figure 3 shown.

[0043] Table 2 Comparative performance of the catalysts of Comparative Examples 1 to 2 in nitrobenzene hydrogenation

[0044]

[0045] According to the test results of Comparative Examples 1 to 2, it is found that unlike Example 1, the metal organic framework in Comparative Example 1 is not soaked in semi-polymerized glucose under low pressure to form a core-shell type composite, but directly pyrolyzes the metal organic framework. It can be seen that the coated core-shell catalyst in Example 1 is better than the uncoated Comparative Example 1, proving the effectiveness of the coating strategy of semi-polymerized glucose forming an amorphous carbon layer at high temperature. The difference between Comparative Example 2 and Example 1 is that no metallic zinc is added during the synthesis of the metal organic framework in Comparative Example 2. Due to the lack of the self-volatilization effect of metallic zinc during the pyrolysis process, the specific surface area of ​​the catalyst is slightly lower than that of the catalyst in Example 1 and there is no honeycomb structure. The addition of zinc will increase the spacing between cobalt atoms in the metal organic framework, reduce the agglomeration of active metals in the catalyst, and the honeycomb structure will also expose more active sites. The combined effect causes the catalytic effect of Comparative Example 1 to be inferior to that of Example 1.

[0046] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and replacement changes can be made without departing from the concept of the present invention, which should be regarded as within the scope of patent protection of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon-coated non-precious bimetallic honeycomb core-shell catalyst, characterized in that: Adding triethylamine to the aqueous solution to enhance the binding force between the metal and the ligand can quickly synthesize a metal organic framework, and then immersing the metal organic framework in a semi-polymerized glucose solution to form a core-shell type composite. The preparation method of the catalyst is implemented according to the following steps: (1) Synthesis of a dual-center metal organic framework: two soluble metal salts are dissolved in deionized water to form a solution A, and imidazole ligands and an appropriate amount of triethylamine are dissolved in deionized water and stirred to form a solution B; solutions A and B are rapidly mixed and stirred for 30 to 120 minutes at room temperature, and then centrifuged, washed, and vacuum dried to obtain a dual-center metal organic framework; (2) Preparation of core-shell composite precursor: Glucose is subjected to low-temperature hydrothermal reaction in a polytetrafluoroethylene-lined reactor to obtain a semi-polymerized glucose solution, which is then transferred to a constant pressure funnel after cooling; the metal organic framework in step (1) is placed in a supported flask and connected to a vacuum pump, which is simultaneously connected to a constant pressure funnel containing the semi-polymerized glucose solution to form a closed low-pressure environment, and the semi-polymerized glucose solution is dripped dropwise, stirred, and the metal organic framework is fully immersed to form a core-shell composite precursor; (3) High temperature calcination process: The core-shell composite precursor in step (2) is centrifugally dried and calcined at 700-1000° C. in a nitrogen atmosphere to volatilize part of the metal zinc. The heating rate is 1-10° C. / min and the calcination time is 0.5-6 h to obtain the catalyst.

2. The method for preparing the catalyst according to claim 1, characterized in that: One metal salt in step (1) is zinc nitrate and its hydrate, and the other is at least one of cobalt nitrate, cobalt acetate, cobalt chloride, ferric nitrate, ferric chloride, nickel nitrate, nickel acetate, nickel chloride and its hydrate; the ligand is at least one of 2-methylimidazole, 2-nitroimidazole and imidazole-2-carboxaldehyde; the molar concentration ratio of the bimetal to the ligand is 1:(2-40); the molar concentration of the added triethylamine in the reaction system is 0.001-0.

006.

3. The method for preparing the catalyst according to claim 1, characterized in that: In step (2), the mass volume ratio of glucose to water is 2-8 g:60 mL, the hydrothermal reaction temperature is 120-170° C., and the reaction time is 6-24 h; the mass volume ratio of the metal organic framework to the semi-polymerized glucose solution is 1 g:(4-20) mL.

4. Use of the catalyst obtained by the method according to any one of claims 1 to 3 in the preparation of aniline by hydrogenation of nitrobenzene, characterized in that: Using hydrogen as a hydrogen source, a catalyst, a solvent and nitrobenzene are mixed in a closed polytetrafluoroethylene-lined reactor, and aniline is obtained by magnetic stirring; the mass ratio of the catalyst to nitrobenzene is 1:(3-20), and the solvent is selected from at least one of methanol, ethanol, propanol, isopropanol and water.

5. The use according to claim 4, characterized in that: The mass volume ratio of nitrobenzene to solvent is (0.1-0.6) g: (10-30) mL; the hydrogen pressure is 0.4-1.2 MPa, the reaction temperature is 50-120° C., and the reaction time is 0.5-4 h.

Citation Information

Patent Citations

  • Preparation method of non-noble metal supported carbon catalyst and application of non-noble metal supported carbon catalyst in preparation of furfuryl alcohol through furfural hydrogenation

    CN117181225A

Cited By

  • Synthesis process of basic cobalt carbonate

    CN121698393A